Gene expression responses of threespine stickleback to salinity: implications for salt-sensitive hypertension - Wang, Gang; Yang, Ence; Smith, Kerri J.; Zeng, Yong; Ji, Guoli; Connon, Richard; Fangue, Nann A.; Cai, James J. (Frontiers in Genetics, 2014)
Despite some recent success with genome-wide association studies (GWAS), identifying hypertension (HTN)-susceptibility loci in the general population remains difficult. Here, we present a novel strategy to address the challenge by studying salinity adaptation in the threespine stickleback, a fish species with diverse salt-handling ecotypes. We acclimated native freshwater (FW) and anadromous, saltwater (SW) threespine sticklebacks to fresh, brackish, and sea water for 30 days, and applied RNA sequencing to determine the gene expression in fish kidneys. We identified 1,844 salt-responsive genes that were differentially expressed between FW sticklebacks acclimated to different salinities and/or between SW and FW sticklebacks acclimated to full-strength sea water. Significant overlap between stickleback salt-responsive genes and human genes implicated in HTN was detected (P < 10-7, hypergeometric test), suggesting a striking similarity in genetic mechanisms of salt handling between threespine sticklebacks and humans. The overlapping genes included a newly discovered HTN gene—MAP3K15, whose expression in FW stickleback kidneys decreases with salinity. These also included genes located in the GWAS loci such as AGTRAP-PLOD1 and CYP1A1-ULK3, which contain multiple potentially causative genes contributing to HTN susceptibility that need to be prioritized for study. We show evidence that stickleback salt-responsive genes provide valuable information facilitating the identification of human HTN genes. We conclude that threespine sticklebacks may be used as a model, complementary to existing animal models, in human HTN research.